Stimuli responsive biopolymer (chitosan) based blend hydrogels for wound healing application. (1st January 2019) - Rasool, Atta; Ata, Sadia; Islam, Atif
Graphical abstract: Highlights: Stimuli responsive chitosan PVP hydrogel are prepared for wound healing applications. Thermal analysis showed hydrogel as thermally more stable than individual chitosan and PVP. Antimicrobial analysis revealed antibacterial activity against E. coli. The hydrogels showed responsive swelling behavior against different media. The distinctive pH behavior of hydrogels showed significant release profile (91.2%) of silver sulfadiazine in PBS. Abstract: Stimuli responsive chitosan (CS) and poly (N-vinyl-2-pyrrolidone) (PVP) have attained hydrogel properties in the presence of 74% neutralized poly acrylic acid (PAA) which can be exploited for wound healing applications. The FTIR spectra confirmed the presence of all specific functional groups and the developed interactions in the hydrogels. The thermal analysis explained that the hydrogel samples are thermally more stable than individual chitosan and PVP. The antimicrobial analysis revealed that all the samples show antibacterial activity against E. coli and the biodegradation analysis is performed to confirm the hydrogels degradation. The hydrogels showed enhanced responsive swelling behavior against different media depending upon the amount of PVP. The %age swelling in water is decreased with the increase in the amount of PVP. The most considerable swelling behavior is observed against pH, as they manifested low swelling at acidic pH and high swelling at neutral pH while at pH 8, the prominent values are obtained. This distinctive behavior of hydrogels and their biocompatibility made them pertinent to drug delivery and their release profile is examined spectrophotometrically using silver sulfadiazine (antibiotic for burnt wounds) showed 91.2% of drug release for a period of 1 h in phosphate buffer saline (PBS) in a consistent and controlled manner.